(untitled) (Research, Society and Development, 2020)
Introduction: The SARS-CoV-2 related coronavirus has spread to almost every country, causing the COVID-19. The severity of COVID-19 is based on the inflammation caused by the cytokine storm. Inflammatory markers suggest a molecular explanation for the occurrence of severe disease and represent a possible treatment. Objective: This review aims to analyse the plausibility of using oral supplementation with immunonutrients. Discussion: Immunonutrition studies the interactions between nutrition, the immune system, infection, and inflammation of tissues. Arginine is a fundamental amino acid in processes of metabolic stress. Its deficiency implies in the capacity of immune response. ω-3 fatty acids demonstrated improved lung compliance, oxygenation, mechanical ventilation time and intensive care unit stay in patients with acute respiratory distress syndrome. Essential for cell-mediated immunity and T lymphocyte function, dietary nucleotides have been shown to improve the cytotoxicity of natural killer cells. Considering that the inversely proportional relationship between presence of IL-6 and TNF-α and the function of T cells is well established in patients with COVID-19, this reinforces the idea that the release control of these biomarkers can be a way to treat this disease. Conclusion: In this scenario, this review raises the possibility of using immunonutrition to improve immune response of individuals affected by COVID-19.